2013
DOI: 10.1039/c3np70047j
|View full text |Cite
|
Sign up to set email alerts
|

Natural sesquiterpenoids

Abstract: This review covers the isolation, structural determination, synthesis and chemical and microbiological transformations of natural sesquiterpenoids. The literature from January to December 2012 is reviewed, and 471 references are cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
105
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(105 citation statements)
references
References 465 publications
(294 reference statements)
0
105
0
Order By: Relevance
“…All these data suggested that compound 1 was a bisabolane sesquiterpenoid containing an -lactam ring. 5 Fortunately, a single crystal X-ray diffraction experiment not only confirmed the structure of compound 1 but also determined the absolute configuration ( Figure 3). Therefore, compound 1 was established to be daedatrin A, as shown.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…All these data suggested that compound 1 was a bisabolane sesquiterpenoid containing an -lactam ring. 5 Fortunately, a single crystal X-ray diffraction experiment not only confirmed the structure of compound 1 but also determined the absolute configuration ( Figure 3). Therefore, compound 1 was established to be daedatrin A, as shown.…”
Section: Resultsmentioning
confidence: 98%
“…Their structures have been elucidated on the basis of spectroscopic methods, especially 2D NMR experiments and X-ray crystallography. A noteworthy feature of bisabolane sesquiterpenoids is the preponderance of a six-membered carbon ring, 5 and compound 4 which have been reported in this article is interesting due to the degraded carbons of the side chain. Furthermore, all compounds were evaluated for their cytotoxicities against five human cancer cell lines.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…6,7) Thus, p-toluenesulfonic acid (p-TsOH) was used as a protonic acid in tetrahydrofuran (THF)/H 2 O (9 : 1) or acetone/H 2 O (9 : 1) but again, no cyclization product was afforded. Scandium and ytterbium trifluoromethanesulfonate (Sc(OTf) 3 and Yb(OTf) 3 ) are often used as Lewis acid catalysts in aqueous organic reactions. 32,33) However, the expected cyclization reaction did not occur when 1 was treated with these Lewis acids.…”
Section: Resultsmentioning
confidence: 99%
“…13 C-NMR spectra were measured at 100 MHz. The chemical shifts are reported in ppm, relative to tetramethylsilane (δ=0.0) or the central line of a triplet at 77.0 ppm for CDCl 3 . IR spectra were measured on a JASCO FT/IR-230 spectrometer.…”
Section: Methodsmentioning
confidence: 99%